PELAKSANAAN GANTI RUGI SENGKETA TANAH DALAM PROYEK INFRASTRUKTUR PEMBANGUNAN JALUR KERETA CEPAT JAKARTA-BANDUNG - Sukmaningrum, Deva; Soediro (Collegium Studiosum Journal, 2024)
The purpose of this research is to provide an explanation of the implementation of compensation in infrastructure projects. The research methods used are normative and empirical juridical legal research methods. Land is a basic human need that is very important in human life. Indonesia's population growth is increasing rapidly, so there is little land available to meet the needs of the community. However, the government must carry out development to provide adequate infrastructure for the community to better support their lives. In carrying out development, especially for the public interest, it is often necessary to use land from the community. The community land can be used for development purposes through the process of land acquisition for public interest. During the land acquisition process, the most important thing is the agreement between the agency that needs the land and the landowning community to determine the form and amount of compensation. Compensation is a proper and fair replacement to the rightful party in the land acquisition process. Land acquisition is very important for infrastructure development, one of which is the construction of a railway line. The government has the legitimacy to take over land owned by individuals or legal entities for the construction of the Jakarta-Bandung High Speed Railway. The construction of the Jakarta-Bandung High Speed Railway is a public project that requires a land acquisition process. The land acquisition process can run smoothly with appropriate compensation.